EDUKASI PEMBUATAN VCO SEBAGAI UPAYA PENINGKATAN NILAI TAMBAH KELAPA DI JEMAAT GPM LUMAHPELU KECAMATAN TANIWEL TIMUR, KABUPATEN SERAM BAGIAN BARAT - Grace Sipahelut, Sophia (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Hein Namotemo, 2026)
This community service activity aims to improve the community's knowledge and skills in processing coconuts into Virgin Coconut Oil (VCO) as a value-added product. The activity was carried out at the GPM Lumahpelu Congregation, Taniwel District, West Seram Regency, involving 20 participants. The methods used included preparation, counseling, and evaluation. The counseling was carried out through the delivery of material on the nutritional content of VCO and its potential as a functional food ingredient, and VCO processing techniques, supplemented by discussions and questions and answers. The results of the activity showed an increase in participants' knowledge and understanding regarding the use of coconuts and the VCO production process.. Evaluation of the activity through questionnaires and interviews indicated that this program had a positive impact on increasing community capacity. This activity contributed to encouraging community empowerment and increasing the economic value of coconuts, although further mentoring is needed to ensure the sustainability of the VCO business development.